Employee loyalty during slowdown of Covid-19: Do satisfaction and trust matter?. Issue 1 (11th October 2021) - Aristana, I Nengah; Arsawan, I Wayan Edi; Rustiarini, Ni Wayan
Abstract : Purpose: This research aims to test employee loyalty in the hotel industry, particularly during the Covid-19 pandemic. This study examines the relationship between leader support in building job satisfaction, trust and employee loyalty. Also, this research aims to test and explain the role of satisfaction and trust as mediator variables. Design/methodology/approach: This research used a quantitative design by distributing questionnaires to 206 employees of the 97 hotels in Bali, Indonesia, particularly during pandemic Covid-19. The research data were then analyzed by using WarpPLS software. Findings: The results revealed that leader support did not have a significant effect on loyalty. Satisfaction and trust act as double mediators in leaders' support and loyalty relationships. Research limitations/implications: Employees need leaders' support to remain loyal to their organization in a slowdown situation due to the Covid-19 pandemic and its various challenges. Originality/value: Research on the effects of the Covid-19 pandemic on various sectors has been comprehensive. However, the research that invests in employee loyalty in the hospitality industry is still rare. This study analyzes the loyalty of hotel employees, particularly when the tourism sector is experiencing a slowdown. This study also examines the role of trust and satisfaction as mediating relationships between leaders' support and loyalty, which have not been widely analyzed in previous studies.